Light-Controlled Cell Factories: Employing Photocaged Isopropyl-β-d-Thiogalactopyranoside for Light-Mediated Optimization of lac Promoter-Based Gene Expression and (+)-Valencene Biosynthesis in Corynebacterium glutamicum - Binder, Dennis (Appl Environ Microbiol, 2016)
Precise control of microbial gene expression resulting in a defined, fast, and homogeneous response is of utmost importance for synthetic bio(techno)logical applications. However, even broadly applied biotechnological workhorses, such as Corynebacterium glutamicum, for which induction of recombinant gene expression commonly relies on the addition of appropriate inducer molecules, perform moderately in this respect. Light offers an alternative to accurately control gene expression, as it allows for simple triggering in a noninvasive fashion with unprecedented spatiotemporal resolution. Thus, optogenetic switches are promising tools to improve the controllability of existing gene expression systems. In this regard, photocaged inducers, whose activities are initially inhibited by light-removable protection groups, represent one of the most valuable photoswitches for microbial gene expression. Here, we report on the evaluation of photocaged isopropyl-β-d-thiogalactopyranoside (IPTG) as a light-responsive control element for the frequently applied tac-based expression module in C. glutamicum. In contrast to conventional IPTG, the photocaged inducer mediates a tightly controlled, strong, and homogeneous expression response upon short exposure to UV-A light. To further demonstrate the unique potential of photocaged IPTG for the optimization of production processes in C. glutamicum, the optogenetic switch was finally used to improve biosynthesis of the growth-inhibiting sesquiterpene (+)-valencene, a flavoring agent and aroma compound precursor in food industry. The variation in light intensity as well as the time point of light induction proved crucial for efficient production of this toxic compound. IMPORTANCE Optogenetic tools are light-responsive modules that allow for a simple triggering of cellular functions with unprecedented spatiotemporal resolution and in a noninvasive fashion. Specifically, light-controlled gene expression exhibits an enormous potential for various synthetic bio(techno)logical purposes. Before our study, poor inducibility, together with phenotypic heterogeneity, was reported for the IPTG-mediated induction of lac-based gene expression in Corynebacterium glutamicum. By applying photocaged IPTG as a synthetic inducer, however, these drawbacks could be almost completely abolished. Especially for increasing numbers of parallelized expression cultures, noninvasive and spatiotemporal light induction qualifies for a precise, homogeneous, and thus higher-order control to fully automatize or optimize future biotechnological applications.